2017
DOI: 10.1111/icad.12234
|View full text |Cite
|
Sign up to set email alerts
|

Large solitary oaks as keystone structures for saproxylic beetles in European agricultural landscapes

Abstract: Abstract. 1. Trees outside forests (TOFs) are declining in agricultural landscapes worldwide. Although they provide valuable habitats for saproxylic species, their relative contribution to saproxylic biodiversity with respect to forests is poorly known. Our aim was to investigate the conservation value of oak TOFs for saproxylic beetles in European agricultural landscapes.2. In our design, plots pairing forest trees and TOFs were sampled in sites nested in two French regions. We studied local habitat condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 57 publications
2
37
1
1
Order By: Relevance
“…Veteran trees are keystone structures in forest, agricultural landscapes, and urban areas (Lindenmayer, Laurance, & Franklin, ; Müller, Jarzabek‐Müller, Bussler, & Gossner, ; Parmain & Bouget, ). The size and age of veteran trees, as well as their coarse bark, structurally complex canopies, and sheltered nutrient‐rich cavities provide features that support high biodiversity (Lindenmayer et al, ; Parmain & Bouget, ). However, veteran trees are in decline globally as a result of intensification of land use and the abandonment of traditional management (Siitonen & Ranius, ).…”
Section: Introductionmentioning
confidence: 99%
“…Veteran trees are keystone structures in forest, agricultural landscapes, and urban areas (Lindenmayer, Laurance, & Franklin, ; Müller, Jarzabek‐Müller, Bussler, & Gossner, ; Parmain & Bouget, ). The size and age of veteran trees, as well as their coarse bark, structurally complex canopies, and sheltered nutrient‐rich cavities provide features that support high biodiversity (Lindenmayer et al, ; Parmain & Bouget, ). However, veteran trees are in decline globally as a result of intensification of land use and the abandonment of traditional management (Siitonen & Ranius, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many saproxylic beetles including the three studied species though require open canopy conditions or depend on shade‐intolerant trees (Albert et al., ; Dubois & Vignon, ; Dubois et al., ; Ranius, ). Even if some veterans occur in shady forests, they are thus unlikely to harbour numerous species associated with veteran trees from more open conditions (Parmain & Bouget, ).…”
Section: Discussionmentioning
confidence: 99%
“…Open-grown, large and hollow trees are keystone ecological structures sustaining woodland biodiversity (Lindenmayer et al, 2012(Lindenmayer et al, , 2014Manning, Fischer, & Lindenmayer, 2006;Müller, Jarzabek-Müller, Bussler, & Gossner, 2014;Siitonen & Ranius, 2015). Recently, more studies have revealed that trees in open conditions are especially important for saproxylic beetles as they host diverse communities with more red-listed species than trees in closed-canopy conditions (Horak et al, 2014;Parmain & Bouget, 2017;Sebek et al, 2016). Although even veterans in closed-canopy conditions may harbour rich saproxylic communities (Parmain & Bouget, 2017), these communities are usually characterized by diverse species composition containing rather generalist species and fewer red-listed individuals (Sebek et al, 2016).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Although most of the saproxylic species associated with large, veteran trees are also at least occasionally able to utilize small trees (Sláma, 1998;Harvey et al, 2011;Chiari et al, 2013), it is the large trees that are likely to host the bulk of their populations and increase the probability of their survival. This is probably one of the main reasons for the great importance of large trees for C. cerdo (Buse et al, 2007;Albert et al, 2012) and probably also saproxylic biodiversity as a whole (Eckelt et al, 2018;Parmain & Bouget, 2018).…”
Section: Diameter Of Inhabited Trees and The Importance Of Large Treesmentioning
confidence: 99%